Experiments and numerical simulation on the influence of pier scour on pipeline safety: a case study of Hang-Yong high-speed line. (17th December 2021) - Huang, Panyang; Li, Zongyu; Dong, Haiyang; Chong, Lin; Chen, Fanjun
ABSTRACT: Changes in the water flow field will occur around bridge piers, leading to local scouring. When pipelines intersect bridge piers, this kind of scour may cause pipeline exposure or even suspension, thereby influencing the safety of pipelines. Experiments and numerical simulations were conducted to calculate the local scour depth around piers. This paper focuses on the influence of scour around the bridge piers and its hazards to the downstream submarine pipelines. The scour elevation could be used to estimate the influence of bridge piers on the safety of submarine pipelines. Three types of bridge piers were included in this numerical model. In order to ensure the safety of submarine pipelines, it is necessary to arrange the bridge piers and pipelines reasonably, and to monitor the scour at pipelines.